The Societal Impact of Digital Technologies and Social Media - Djo Day, Yulyanti; Dominikus, Yohanes; Laurensius, Adrianus (Journal Social Humanity Perspective, 2023)
The massive use of digital technologies and social media platforms during the digital era has ushered in a new era of societal transformation. This study explores the complex effects of the digital age on a range of societal issues, such as identity construction, interpersonal relationships, activism, information sharing, and the digital divide. This study provides important insights into the complexity and nuances of the digital landscape by examining the experiences of various participants from a range of age groups, genders, and socioeconomic backgrounds. The results show that the digital age has fundamentally changed how people create their identities by giving them access to previously unheard-of chances for self-expression and exploration through social media platforms and online groups. Nevertheless, there are moral questions about data privacy, permission, and responsible digital activity. Social interactions have changed significantly as a result of people communicating and interacting with each other online. This raises concerns about the quality and authenticity of these connections as well as the possibility of both beneficial and negative consequences on mental health. The study goes into further detail about how social movements and activism are affected by digital technologies. While the digital era has helped spread information and amplified activists' voices, participants also highlight problems like false information and the necessity for a comprehensive strategy that unifies physical and online activism initiatives. With persons from various socioeconomic backgrounds having varying access to digital tools and possibilities, the